KEANEKARAGAMAN SERANGGA DEKOMPOSER DI TEMPAT PEMBUANGAN AKHIR (TPA) MUARA FAJAR UNTUK RANCANGAN BUKU SAKU BIOLOGI MATERI KEANEKARAGAMAN HAYATI KELAS X SMA - Cici Yurianti; Suwondo Suwondo; Elya Febrita (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2022)
Abstract: This research was conducted to determine the diversity ofdecomposer insects at the Muara Fajar Final Disposal Site (TPA) of West RumbaiDistrict, Pekanbaru City as a biology pocket book design for class X SMA. Decomposerinsects were sampled using purposive random sampling. As for the identification ofinsects, it was carried out at the Laboratory of the Biology Education Study Program,the PMIPA FKIP Department, Riau University. Parameters measured were speciescomposition, diversity index, and dominance index of decomposer insects. While thephysical-chemical parameters include the degree of acidity (pH), soil temperature, soilmoisture, and light intensity. The data were analyzed descriptively, with the result thatthe composition of the decomposer insects found at the Muara Fajar Final DisposalSite, West Rumbai District, Pekanbaru City consisted of 7 orders, 13 families, 20species with a total of 3103 individuals. Meanwhile, the diversity index of decomposerinsect species was moderate with index values ranging from 1 to 3. The highest diversityindex was found at station II (H'=2.447), and the lowest at station III (H'=2.078). Theresults of the research were used as a design pocket book for class X high schoolbiology learning to enrich learning resources on biodiversity material.Key Words : Decomposer Insects, Pocket Books, Muara Fajar Final Disposal Site (TPA)